2008
DOI: 10.1111/j.1365-2141.2008.07177.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA‐DPB1 allelic and single amino acid mismatches on HSCT

Abstract: SummaryThe interpretation of the role of HLA-DPB1 in unrelated haematopoietic stem cell transplantation (HSCT) is subject to discussion. We have investigated the role of HLA-DPB1 allele matching in HSCT outcomes in 161 recipients who were HLA-A, -B, -C, -DRB1 and -DQB1-matched with their unrelated donors at the allelic level (10/10). In addition, we analysed the association of polymorphic amino acid mismatches of DPB1 molecule with HSCT end-points, and a previously published permissiveness concept. HLA-DPB1 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 27 publications
4
40
1
Order By: Relevance
“…Evidence for a role of HLA-DPB1 mismatches is now well documented. 6,13,[23][24][25] In 10/10-matched HSCT, DRB3 and DRB4 mismatches were associated with poorer outcome, although most donor-recipient pairs were also incompatible for the DPB1 locus. 16 7/8-matched HSCT more than two mismatches at the DP, DQ and DRB3/4/5 loci were associated with an increased risk of mortality.…”
Section: Impact Of Single Mismatchesmentioning
confidence: 99%
“…Evidence for a role of HLA-DPB1 mismatches is now well documented. 6,13,[23][24][25] In 10/10-matched HSCT, DRB3 and DRB4 mismatches were associated with poorer outcome, although most donor-recipient pairs were also incompatible for the DPB1 locus. 16 7/8-matched HSCT more than two mismatches at the DP, DQ and DRB3/4/5 loci were associated with an increased risk of mortality.…”
Section: Impact Of Single Mismatchesmentioning
confidence: 99%
“…In the blood samples obtained for tissue typing, DNA was isolated either by salting-out method or GenoMTM-6 (GenoVision; VertriebsGesmbH, Vienna, Austria). HLA class II genes were typed at the high-resolution level by sequence-based typing and comprised HLA DRB1, DRB3/4/5, and DQB1 allele (21).…”
Section: Hla Class II Typingmentioning
confidence: 99%
“…Based on cross-reactive T-cell alloreactivity patterns, our group has previously described an algorithm for nonpermissive HLA-DPB1 mismatches, which were shown by us and subsequently by others to be significantly associated with transplant-related mortality but not with overall mortality (OM). [9][10][11] In the present study, we have modified this algorithm by integrating our functional data with those reported by others [12][13][14] and tested its clinical predictive value by retrospective analysis of 621 unrelated HSCT facilitated through the Italian Bone Marrow Donor Registry. The results provide compelling evidence that the clinical outcome of unrelated HSCT can be significantly improved by consideration of nonpermissive HLA-DPB1 disparity in donor selection.…”
Section: Introductionmentioning
confidence: 99%